2019
DOI: 10.1093/aje/kwz069
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Gun Laws and Suicides

Abstract: We examined the impact of a state gun law environment on suicides overall and within demographic subgroups. We linked 211,766 firearm suicides and 204,625 nonfirearm suicides in the 50 states of the United States for 2005–2015 to the population in each state, year, race/ethnicity, sex, and age, as well as to an index of state-level gun control. Difference-in-differences, zero-inflated, negative-binomial models were used to evaluate the impact of strengthening gun control on firearm and nonfirearm suicides. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…This study supports the hypothesis that states with a higher number of firearm-related laws had lower rates of firearm-related suicides among older adults compared with states with fewer firearm laws, building on previous work that has found this same relationship in the general population 13 . However, there appeared to be a slight increase in non-firearm-related suicides in this age group, which was also seen in a recent study by Ghiani et al (2019), although they observed no impact on state firearm-related laws on non-firearm suicides overall 15 . Those results differ from those reported here, which found a significant association between the number of gun laws and fewer overall suicides.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study supports the hypothesis that states with a higher number of firearm-related laws had lower rates of firearm-related suicides among older adults compared with states with fewer firearm laws, building on previous work that has found this same relationship in the general population 13 . However, there appeared to be a slight increase in non-firearm-related suicides in this age group, which was also seen in a recent study by Ghiani et al (2019), although they observed no impact on state firearm-related laws on non-firearm suicides overall 15 . Those results differ from those reported here, which found a significant association between the number of gun laws and fewer overall suicides.…”
Section: Discussionsupporting
confidence: 82%
“…The impact on non-firearm suicides is less clear. In one study examining the impact of state gun laws on both firearm and non-firearm suicides, there was a reduction in firearm suicides but not in non-firearm suicides in the population as a whole 15 . Among older individuals, however, there was an increase in non-firearm suicides seen 15 , raising concerns about whether additional policies are needed for subgroups who may shift to non-firearm suicides.…”
Section: Introductionmentioning
confidence: 99%
“…Multilple comparisons have found states with more restrictive firearm legislation to have lower pediatric, unintentional, suicide, and overall firearm-related fatality rates, and more slowly rising suicide rates. [11][12][13][14][15] A casecontrol study of firearms in events identified by medical examiner and coroner offices from 37 counties in Washington, Oregon, and Missouri, and 5 trauma centers in Seattle, Spokane, Tacoma, and Kansas City found that 4 practices of keeping a gun locked, unloaded, storing ammunition locked, and in a separate location are each associated with a protective effect for firarm injuries in homes with children and teenagers where guns are stored. 16 Having a gun in the home is associated with an increased firearm death risk for everyone in the home, including <5 year-olds.…”
Section: Discussionmentioning
confidence: 99%
“…Following other studies (1,11,15), the independent variable was the rearm law strength score, an unweighted count of state-level rearm laws, with higher scores denoting more laws regulating rearms and fewer laws deregulating rearms (e.g. law providing blanket immunity to rearm manufacturers).…”
Section: Independent Variablesmentioning
confidence: 99%